PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) MATERI IPA BAGIAN TUBUH TUMBUHAN TERHADAP PENINGKATAN HASIL BELAJAR PESERTA DIDIK KELAS IV DI SDN 84 SINGKAWANG - suci nurpitri; Wahyuni Oktavia; Kamaruddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACT Suci Nurpitri: The Effect of Project Based Learning Model (PjBL) on Plant Body Parts Science Material on Improving Learning Outcomes of Grade IV Students at SDN 84 Singkawang. Thesis, ISBI Singkawang, 2025. This pre-experimental quantitative research aims to determine the effect of the Project Based Learning (PjBL) learning model on the learning outcomes of fourth grade students of SDN 84 Singkawang on the science material of plant body parts. All 24 fourth grade students became the research sample. Data were collected through pre-test and post-test. The results showed a difference between learning outcomes before and after the application of PjBL. The average student pre-test score was 62.5, increasing to 73.96 in the post-test, showing an increase of 11.46 points or 18.34%. The effect size calculation results show a value of 0.6535, which is classified as a large interpretation, so the alternative hypothesis (HA) is accepted. In conclusion, the Project Based Learning (PjBL) learning model has a major effect on improving the learning outcomes of fourth grade students of SDN 84 Singkawang on plant body parts science material. Keywords: Project Based Learning, Learning Outcomes, Science